An Assessment of HIV/STI Vulnerability and Related Sexual Risk-Taking in a Nationally Representative Sample of Young Croatian Adults - Štulhofer, Aleksandar (Array, 2009)
Despite the recent increase in the number of HIV infections in Central and Eastern Europe, patterns of sexual behavior have not been extensively researched, particularly among young people. The aim of the present study was to provide a comprehensive assessment of HIV/AIDS-related vulnerability and sexual risk-taking among young adults in Croatia. Data were collected in 2005 using a nationally representative, multi-stage stratified probability sample (n = 1, 093) of women and men aged 18– 24 years. The focus in this article was on predictors of sexual risk-taking measured by a composite risky sexual behaviors scale. Using hierarchical regression models, we analyzed gendered effects of community, family, peer group, and individual level factors. For both men and women, peer pressure, sensation seeking, personal risk-assessment, behavioral intention, condom use at first sexual intercourse, and sexual victimization were significant predictors of sexual risk-taking behaviors. A number of predictors were gender-specific: sexual assertiveness and condom self-efficacy for women and parental monitoring, traditional morality, HIV knowledge, and talking about sex with partner for men. Documenting substantial prevalence of potentially risky sexual behaviors among young people in Croatia, the findings call for prevention and intervention efforts that should focus on individual capacity building for responsible sexual behavior.